SPE Annual Technical Conference and Exhibition 1998
DOI: 10.2118/49270-ms
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Grading in the Ghawar Khuff Reservoirs

Abstract: The paper presents the results of a study to investigate the variation of gas composition and key PVT properties with depth in the Khuff carbonate reservoirs of the Ghawar field in Saudi Arabia. The study was performed as part of a larger effort to characterize the reservoir fluids for compositional simulation and development planning. Laboratory PVT reports on over twenty appraisal wells were used as a basis for the study. It was found that both condensate content and hydrocarbon composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…These are also the first reports of their kind in the literature to the best of our knowledge. Previously, Temeng et al 8 reported a heptane-plus decrease with depth in a hydrocarbon formation in Saudi Arabia without conclusive evidence. Our measurements both in the formation and in the wells (which are connected) confirm the existence of a dense fluid mixture floating on the top of a light fluid mixture.…”
Section: Introductionmentioning
confidence: 95%
“…These are also the first reports of their kind in the literature to the best of our knowledge. Previously, Temeng et al 8 reported a heptane-plus decrease with depth in a hydrocarbon formation in Saudi Arabia without conclusive evidence. Our measurements both in the formation and in the wells (which are connected) confirm the existence of a dense fluid mixture floating on the top of a light fluid mixture.…”
Section: Introductionmentioning
confidence: 95%
“…H 2 S is believed being generated by thermo-chemical sulfate reduction reaction (Temeng et al, 1998). In this process, anhydrite or dissolved sulfate is chemically reduced into H 2 S at the expense of methane and probably hydrocarbons of higher molecular weight (CaSO 4 ϩ CH 4 ¡ CaCO 3 ϩ H 2 S ϩ H 2 O).…”
Section: Introductionmentioning
confidence: 99%
“…3 The non-associated gas is sour with hydrogen sulfide content that varies from 0 to 10 mol%. 4 Wells that produce sour gas with high levels of hydrogen sulfide are completed with low-carbon steel tubulars (L-80 and C-95). To enhance the productivity of these wells both matrix acidizing and acid fracturing treatments were used.…”
Section: Introductionmentioning
confidence: 99%
“…This acid system is also based on HCl/formic and contains a synthetic polymer, a cross-linker, and a breaker, and other acid additives. This acid cross-links over a narrow pH range (2)(3)(4) where its viscosity increases by several order of magnitude. The objectives of this work were to: (1) Determine the advantages of using insitu gelled HCl/formic acid over gelled HCL/formic acid (2) Evaluate field application of in-situ gelled acids to stimulate deep carbonate gas reservoirs, and (3) Optimize the treatment based on lab and field results.…”
Section: Introductionmentioning
confidence: 99%